2020
DOI: 10.3390/su12072872
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Spatial Panel of Subnational GHG Emissions: Environmental Effectiveness of Emissions Taxes in Spanish Regions

Abstract: In this paper we study the effectiveness of environmental taxes and policies of the regional level of government to reduce GHG emissions. We use panel data for the 17 Spanish regions in the period 1999–2017, controlling the spatial nexus between regions and using a dynamic Durbin model. The results show there is spatial dependence and spatio-temporal persistence of GHG emissions at the regional level in Spain, and that in this context, the taxes and policies intended to manage emissions introduce a slight disi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…As for economic policies for controlling CO 2 emissions, it has been proven that emissions taxes are effective tools for the reduction of carbon dioxide emissions [ 26 ]. Measurement models developed by the methodology of the paper can be used to analyze the results of such policies.…”
Section: Discussionmentioning
confidence: 99%
“…As for economic policies for controlling CO 2 emissions, it has been proven that emissions taxes are effective tools for the reduction of carbon dioxide emissions [ 26 ]. Measurement models developed by the methodology of the paper can be used to analyze the results of such policies.…”
Section: Discussionmentioning
confidence: 99%
“…Subscripts i and t represent the province and year, respectively. Vallés and Zárate [46] suggested that the environmental issues needed to be considered from a dynamic perspective, as pollutants in one year depend on the previous year's emissions. The dynamic panel data model reflects the dynamic lag effect by introducing the lag dependent variables.…”
Section: Spatial Convergence Testmentioning
confidence: 99%
“…This narrative describes a future with medium challenges to mitigation and adaptation [26]. Load factor (passengers per vehicle) and door-to-door speed are derived from the GCAM [27] and vehicle cost and energy intensity are taken from the AIM/Enduse model [22]. GDP and population assumption are shown in Figure 2.…”
Section: Basic Socioeconomic and Technological Datamentioning
confidence: 99%
“…The technological feasibility of achieving a 50% reduction of global GHG emissions by 2050 is also proved, where carbon capture and storage, cleaner power generation, and biofuel account for 64% of the total GHG emission reduction [21]. Vallés-Giménez et al [22] studied the effectiveness of environmental taxes in Spanish regions by using panel data and found environmental taxes can be a slight disincentive to generate emissions, while tougher measures are needed to meet EU commitments. Kishimoto et al [23] employed an integrated assessment model in China and found carbon price policy and a stringent emission standard are effective strategies for addressing air pollution.…”
Section: Introductionmentioning
confidence: 99%